Weed Control : Sustainability, Hazards, and Risks in Cropping Systems Worldwide - Korres, Nicholas E.; Burgos, Nilda R.; Duke, Stephen O.; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
In light of public concerns about sustainable food production, the necessity for human and environmental protection, along with the evolution of herbicide resistant weeds, call for a review of current weed control strategies. Sustainable weed control requires an integrated approach based on knowledge of each crop and the weeds that threaten it. This book will be an invaluable source of information for scholars, growers, consultants, researchers and other stakeholders dealing with either arable, row, cash, vegetables, orchards or even grassland-based production systems. The uniqueness of this book comes from the balanced coverage of herbicide effects on humans and environment in relation to best weed control practices of the most important cropping systems worldwide. Furthermore, it amalgamates and discusses the most appropriate, judicious and suitable weed control strategies for a wide range of crops. It reviews the available information and suggests solutions that are not merely feasible but also optimal.
Table of Contents -- PART 1: WEED SCIENCE-SUSTAINABILITY, HAZARDS AND RISKS -- Sustainable agriculture and integrated weed management -- Fabian D. Menalled -- Effects of herbicides on humans -- Nicholas E. Korres -- Effects of weed management on soil ecosystems -- Heather L. Tyler and Martin A. Locke -- Effects of herbicides on freshwater ecosystems -- Gertie Arts, Mark Hanson -- Direct and Indirect Effects of Herbicides on Insects -- John L. Capinera -- Evolution of Herbicide-Resistant Weeds -- Nilda Roma-Burgos, Ian M. Heap, Christopher E. Rouse, and Amy L. Lawton-Rauh -- Microbial Herbicides -- Alan K. Watson -- Natural Product-Based Chemical Herbicides -- Stephen O. Duke, Daniel K. Owens and Franck E. Dayan -- Allelopathy for Sustainable Weed Management -- Yoshiharu Fujji, Kwame Sarpong Appiah -- Genetically Engineered Herbicide Tolerant Crops and Sustainable Weed Management -- Mahima Krishnan, Christopher Preston -- PART 2: SUSTAINABLE WEED CONTROL IN CROPS AND CROPPING SYSTEMS -- Sustainable Weed Control in Small Grain Cereals (Wheat/Barley) -- Alistair J. Murdoch -- Sustainable Weed Control in Maize -- Per Kudsk, Vasileios P. Vasileiadis and Maurizio Sattin -- Grain Sorghum -- Lauren M. Schwartz-Lazaro and Karla L. Gage -- Sustainable Weed Control in Rice -- Khawar Jabran, Ahmet Uludag, and Bhagirath S. Chauhan -- Sustainable weed control in soybean -- Nicholas E. Korres, Krishna N. Reddy, Christopher Rouse, and Andy C. King -- Sustainable Weed Control in Cotton -- Krishna N. Reddy and William T. Molin -- Sustainable Weed Control in Oilseed Rape -- Peter J.W. Lutman -- Sustainable Weed Management in Peanut -- Ramon G. Leon, David L. Jordan, Grace Bolfrey-Arku, and Israel Dzomeku -- Sustainable Weed Control in Tobacco -- Matthew C. Vann, Loren R. Fisher, and Matthew D. Inman -- Sustainable Weed Control in Strawberry -- Steven A. Fennimore and Nathan S. Boyd -- Sustainable Weed Control in Vegetables -- Russell W. Wallace, Timothy W. Miller, and Joseph G. Masabni -- Sustainable Weed Control in Small fruits (to be included) -- Reid J. Smeda -- Sustainable Weed Control in Coffee -- Claudio Pagotto Ronchi, Antonio Alberto da Silva -- Advances in weed management in tea -- Probir Kumar Pal, Sanatsujat Singh and Rakesh Kumar Sud -- Weed Management in Sugarcane -- Ramon G. Leon, D. Calvin Odero -- Sustainable weed control in pineapple -- Victor Martins Maia, Ignacio Aspiaz, and Rodinei Facco Pegoraro -- Sustainable Weed Control in Natural Rubber (To be included) -- Jesusa D. Ortuoste, Nilda R. Burgos -- Sustainable Weed Control in Orchards -- Rakesh S. Chandran -- Sustainable Weed Control in Grapes -- Ilias S. Travlos, Dimitrios J. Bilalis, Nikolaos Katsenios and Rafael De Prado -- Sustainable potato weed management -- Heidi Johnson, Jed Colquhoun -- Sustainable weed control in Sugar Beet (To be included) -- Giovanni Campagna, Daniele Rosini -- Sweetpotato: Important weeds and sustainable weed management -- David W. Monks, Katie M. Jennings, Stephen L. Meyers, Tara P. Smith and Nicholas E. Korres -- Sustainable Weed Control with Aromatic Plants and Essential Oils -- Thomas K. Gitsopoulos, Kalliopi Kadoglidou, and Christos A. Damalas -- Issues and Sustainability in Grassland Weed Control -- Stevan Z. Knezevic, Nevin Lawrence -- Organic Farming and Sustainable Weed Control -- Eric Gallandt, Sonja Birthisel, Bryan Brown, Margaret McCollough and Margaret Pickoff.
Includes bibliographical references and index.
Also available in print format.
Keywords: TECHNOLOGY & ENGINEERING / Agriculture / General; Arable crops; Cash crops; Herbicides and environment; Herbicides and human health; Herbicide resistant weeds; Row crops, Plantation crops, Tropical crops, Root crops, Orchards and vineyards, Grassland, Sustainable food production; Weeds -- Control; Electronic books